2023
DOI: 10.1017/s0954579423000123
|View full text |Cite
|
Sign up to set email alerts
|

Are there negative cycles of peer victimization and rejection sensitivity? Testing ri-CLPMs in two longitudinal samples of young adolescents

Abstract: This study’s aim was to examine whether there are negative increasing cycles of peer victimization and rejection sensitivity over time. Drawing from Social Information Processing Theory, we hypothesized that victimization leads to higher levels of rejection sensitivity, which would put adolescents at risk for higher future victimization. Data were collected in a four-wave study with 233 Dutch adolescents starting secondary education (Mage = 12.7 years), and a three-wave study with 711 Australian adolescents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
0
0
2
Order By: Relevance
“…It demonstrates that boys are more susceptible to emotional abuse then girls. The finding of the present research work is consistent with earlier studies, which reveals that males reported higher levels of rejection sensitivity than females at age 16 and 17 (Kellij et al, 2023;Webb et al, 2014). Another study on Gendered Socialization suggests that adolescent males have a more challenging time transitioning to more emotionally complex, heterosocial friendships and romantic relationships than females (Homroy, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…It demonstrates that boys are more susceptible to emotional abuse then girls. The finding of the present research work is consistent with earlier studies, which reveals that males reported higher levels of rejection sensitivity than females at age 16 and 17 (Kellij et al, 2023;Webb et al, 2014). Another study on Gendered Socialization suggests that adolescent males have a more challenging time transitioning to more emotionally complex, heterosocial friendships and romantic relationships than females (Homroy, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…Bij de mri-taak verscheen telkens een gezicht met emotionele uitdrukking en moest het geslacht van het gezicht beoordeeld worden (van Harmelen et al, 2013). In deze studie (Kellij et al, 2023b) werd geen bewijs gevonden dat slachtofferschap (langdurig of recent) samenhing met een andere verwerking van andermans emoties. Niet in de hersenen, maar ook niet in automatische aandacht.…”
Section: Coderingunclassified
“…Er was een positieve samenhang tussen slachtofferschap en gevoeligheid voor afwijzing. Desondanks resulteerde een verandering in slachtofferschap niet in een verandering in gevoeligheid voor afwijzing, noch andersom (Kellij et al, 2023a).…”
Section: Interpretatieunclassified